P293 Prognosis of small intestinal ulcers (SIUs) on capsule endoscopy when magnetic resonance enterography is normal. (25th January 2019) - González Suárez, B; Castro-Poceiro, J; Fernández-Clotet, A; Feurstein, J; Ricart, E; Falchuk, K; Ordás, I; Rodriguez, S; Pleskow, D; LLach, J; Panés, J; Moss, A
Abstract: Background: Small intestinal ulcers (SIUs) are often identified during capsule endoscopy (CE) in patients whose MR enterography (MRE) is normal during evaluation of established, or suspected, Crohn's disease. The prognostic implications of SIUs in this setting are unknown. Methods: We undertook longitudinal follow-up on a cohort of patients at two academic centres. CE databases were used to identify patients with SIUs and linked to the electronic medical record to identify patients with an MRE within 12 months of the CE study. This cohort was further narrowed to patients with established or suspected Crohn's disease based on ordering details for the CE study. Follow-up data on hospitalisations, emergency visits and clinic visits after the CE study was collected in this cohort. Dichotomous data were analysed by 2 × 2 tables and ×2 or Fisher exact test for significance. Results: We identified 85 subjects with established or suspected CD, a normal MRE, and a completed CE study. Of these, 35 had SIUs (CE+), and 50 did not have SIUs (CE-). Table 1 summarises their baseline characteristics; mean ESR and CRP were similar in both groups. The mean duration of follow-up was 40 months ±27 months. In patients with established CD, CE+ patients had non-significant differences in rates of healthcare visits to CE- patients (60% vs. 45%, p = 0.4), and similar rates of hospitalisation (29% vs. 13%, p = 0.3). In contrast, amongst all patients investigated, CE+ patients were more likely to be hospitalised during follow-up (16% vs. 2%, p = 0.02), or require healthcare visits (49% vs. 16%, p = 0.001) than CE- patients. Conclusions: Symptomatic patients with SIUs on CE, but normal MRE, have increased healthcare utilisation when compared with those without SIUs. Further studies would be required to determine whether this cohort would benefit from therapeutic intervention.